Growing Substrates, Fertilization, and Irrigation for Creeping Bentgrass Establishment on Sand‐Based Putting Greens. Issue 1 (19th October 2017) - Calvache, Sara; Kvalbein, Agnar; Aamlid, Trygve S.
Abstract : Growing substrates, fertilizer inputs, and irrigation are important factors for grow‐in of sand‐based putting greens. The research reported here was triggered by grow‐in problems encountered in 2015 after replacing garden compost with Sphagnum peat in the rootzone on a sand‐based green at the NIBIO Turfgrass Research Center, Norway. A pot trial was conducted with the same type of sand amended with: (i) 20% (v/v) garden compost, (ii) 10% (v/v) Sphagnum peat, (iii) equal volumes of (i) and (ii), (iv) 10% (v/v) Sphagnum peat plus lime (200 g CaCO3 m −2 ), and (v) 10% (v/v) Sphagnum peat plus phosphoric acid, 5 g P m −2 . The amendments were tested with or without preplant application of chicken manure (5 g N and 2.5 g P m −2 ) and at the two irrigation rates: 3 and 12 mm d −1 . The pots were seeded with creeping bentgrass ( Agrostis stolonifera L.), and turfgrass coverage and clipping yields were recorded for 5 wk after seeding. Turfgrass coverage developed significantly faster and clipping yields were significantly higher after amendment with compost than after amendment with peat or peat plus lime. Incorporation of chicken manure did not enhance grow‐in on substrates containing full or half rates of compost but improved grow‐in on peat, especially when combined with phosphoric acid. Excessive irrigation had no impact on turfgrass coverage but reduced clipping yields on substrates containing compost, compost plus peat, or peat plus phosphoric acid. We conclude that the grow‐in problems encountered in 2015 were most likely due to inadequate quality of the Sphagnum peat.